Enhanced hydrogen production by methanol decomposition using a novel rotating gliding arc discharge plasma. Issue 16 (3rd February 2016) - Zhang, Hao; Zhu, Fengsen; Li, Xiaodong; Cen, Kefa; Du, Changming; Tu, Xin
Abstract : Hydrogen production from methanol decomposition was performed in a novel direct current (DC) rotating gliding arc (RGA) plasma reactor. Abstract : Hydrogen production from methanol decomposition was performed in a novel direct current (DC) rotating gliding arc (RGA) plasma reactor. The effects of various important parameters (feed flow rate, applied voltage, CH3 OH concentration, operating current, preheating temperature, and water addition) on the reaction performance of the plasma methanol decomposition were investigated. The results showed that increasing the applied voltage and the operating current remarkably enhanced the CH3 OH conversion in contrast to the effects of increasing feed flow rate, CH3 OH concentration, and water addition. The selectivities of gas products (primarily H2 and CO) appeared to be positively correlated with the specific energy input. A comparison of the methanol decomposition processes using different non-thermal plasmas ( e.g., dielectric barrier discharge and corona discharge) clearly showed that the RGA plasma provided a significantly higher CH3 OH conversion (28.6–95.6%) and a relatively high energy yield of H2 (8.5–32.0 g kW −1 h −1 ) while maintaining a processing capacity that was several orders of magnitude higher than the other plasmas. A mathematical model was established to predict the CH3 OH conversion and energy yield of H2 . The model sensitivity analysis indicated that the CH3 OH concentration was the most influential parameter, whereas the water addition was the least important parameter for the reaction performance.